Engineering Mycolicibacterium neoaurum for the production of antioxidant ergothioneine. Issue 1 (28th March 2022) - Xiong, Liang‐Bin; Xie, Zhi‐Yong; Ke, Jie; Wang, Li; Gao, Bei; Tao, Xin‐Yi; Zhao, Ming; Shen, Ya‐Ling; Wei, Dong‐Zhi; Wang, Feng‐Qing
Abstract: Ergothioneine (EGT) represents valuable protective functions for humans, but EGT from the diet cannot meet daily requirements. Although the heterologous synthesis of EGT had been achieved, it is still a challenge to obtain stable and high‐yield EGT‐producing cell factories. Here, after the co‐overexpression of the EGT synthetic gene cluster and hisG, hisC, and allB1 in Mycolicibacterium neoaurum, the natural EGT titer was increased by 7.2‐folds. However, the degradation problem of EGT in large‐scale fermentation needs to be urgently solved. A putative lyase gene Mn_3042 was inactivated, thus inhibiting the product degradation and increasing the EGT titer by 21%. Moreover, the enhancement of S ‐adenosyl‐ l ‐methionine regeneration further increased EGT titer by 28%. After optimization of fed‐batch fermentation, the yield of EGT was boosted to 1.56 g/L with a productivity of 7.2 mg/L/h. This study provides a systematic engineering strategy for developing EGT‐producing cell factories. Abstract : M. neoaurum was systematically engineered to produce ergothioneine. Regulating of a lyase and SAM regeneration boosted the production of ergothioneine. The engineered M. neoaurum realized the production of 1.56 g/L ergothioneine.